Creating Judaism history, tradition, practice - Satlow, Michael L. 1964- (New York Columbia University Press, 2006)
Introduction -- Promised lands -- Creating Judaism -- Between Athens and Jerusalem -- The rabbis -- Rabbinic concepts -- Mitzvot -- The rise of reason -- From Moses to Moses -- Seeing God -- East and West -- Epilogue: Whither Judaism?
Promised lands -- Creating Judaism -- Between Athens and Jerusalem -- The rabbis -- Rabbinic concepts -- Mitzvot -- The rise of reason -- From Moses to Moses -- Seeing God -- East and West -- Whither Judaism?
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Judaism; Jews -- Identity; Jews -- Identity